The Analysis and Visualization of 3 Dimensional Dissection Table in Anatomy Teaching in Cross-Section Images as Per Student’s Perspective (Medical Forum Monthly, 2023)
Objective: To find student’s perception in relation to the anatomy learning with 3D visualization of whole human body.Study Design: Prospective cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Anatomy, Jinnah Sindh Medical University, Karachi from August 2019 to February 2020.Materials and Methods: The study was conducted after 4 weeks of teaching on spectra 3D visualize Table of 1st year MBBS students of Jinnah Sindh Medical University (n=120). After the period of teaching, a questioner of closed-ended questions was filled by the student and frequency was calculated on those responses. Chi-square was applied for the demographic data to assess the student perspective.Results: 73.4% of the population was agreed on that it is an easy mode of learning and 62.5% and 71% were agreed that they gained spatial knowledge of cross section viscera thru this table, 50% students were agreed that the 3 D images were adequately appreciated regarding the regional anatomy, most of the students felt motivated while using this technologyConclusion: 3D image and touch technology will help the student for a better understanding of anatomy teaching and provide an interactive method of teaching. This technology will improve the student learning and knowledge of anatomy.